Best practice in questioning child witnesses in Malaysia / Amirul Irfan Ahmad Badaruddin, Farah Nasuha Sudarman and Fatin Syafira Ahmad Zulkifli - Ahmad Badaruddin, Amirul Irfan; Sudarman, Farah Nasuha; Ahmad Zulkifli 2, Fatin Syafira (2012)
This research analysed the weaknesses of the current practise on questioning techniques used for child witnesses and to give recommendation with the intention to increase the reliability and the quality of evidence given by a child witness. The First chapter discussed the research objectives, methodology, scope and limitations and problem statement. In addition, all the necessary conceptual features are introduced to ensure the readers to understand about the research. The second chapter explained on the psychological state and capabilities of a child that needs to be understand before questioning a child witness. In the third chapter, the researchers pointed out other relevant factors that may affect the accuracy of evidence given by a child witness. The fourth chapter discussed on the findings based on several semi-structured interviews. Our research concludes with recommendations in guiding to better techniques in questioning a child witness and other methods that may help in increasing the accuracy of evidence given by children.